2020
DOI: 10.1016/j.heliyon.2020.e04357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preparation method on the biochemical characterization and cytotoxic activity of New Zealand surf clam extracts

Abstract: Molluscan extracts confer a wide range of health promoting properties, one of them is cytotoxicity. Extraction and processing can affect the efficacy and properties of bioactive molecules. New Zealand (NZ) surf clams have never been thoroughly studied for bioactives until recently. However, the effect of cold and heat extraction procedure on biochemical composition and cytotoxic activities of NZ surf clam remains unanswered. The objective is to compare the effects on cytotoxicity of three NZ surf clams (Diamon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, heat treatment of flavonoids might cause activity change. It has been identified that the heated vegetable juices had decreased anti-proliferative activity against the HL-60 cell line ( Roy et al, 2007 ), while the cold-processed surf clam extracts showed better anti-tumor activity in seven cancer cell lines than the heat-processed extracts ( Odeleye et al, 2020 ). In addition, the thermal processing of lactoferrin had an impact on its ability to inhibit the LPS-induced NF-κB activation ( Goulding et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, heat treatment of flavonoids might cause activity change. It has been identified that the heated vegetable juices had decreased anti-proliferative activity against the HL-60 cell line ( Roy et al, 2007 ), while the cold-processed surf clam extracts showed better anti-tumor activity in seven cancer cell lines than the heat-processed extracts ( Odeleye et al, 2020 ). In addition, the thermal processing of lactoferrin had an impact on its ability to inhibit the LPS-induced NF-κB activation ( Goulding et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Sea cucumber protein hydrolyzate demonstrates not only the reduction of ROS accumulation in cells but also directly scavenge free radicals. Odeleye et al., 2020 ; Suleria et al., 2015 ). Guo et al., 2020 .…”
Section: Immune Functions Of Aquafood Compoundsmentioning
confidence: 99%
“…which have potential antiviral potency. Extracts or compounds isolated from different types of marine invertebrates possess anticancer, anti-helmintic, antihypertensive, antifungal, antiviral, antibacterial, and immune modulatory properties ( Odeleye et al., 2020 ; Suleria et al., 2015 ). Marine mussels from Mytilidae family contain different bioactive compounds such as protein, lipid, carbohydrate, PUFAs, and iodine which show antimicrobial and anti-inflammatory activity.…”
Section: Immune Functions Of Aquafood Compoundsmentioning
confidence: 99%